ANALYSIS OF ABDULLAH NASHIH ULWAN'S METHOD IN TEACHING RELIGIOUS AND MORAL VALUES TO EARLY CHILDHOOD: ANALYSIS OF JOURNAL SINTA 2-5 - novitasari, Nurul (Universitas Al-Hikmah Indonesia, 2024)
Strengthening children's mental potential and instilling religious moral values ​​is carried out in various ways provided by educator Abdullah Nashih Ulwan such as methods of example, habituation, advice, attention and supervision, and punishment. Religious moral values ​​play a role in determining children's behavior so that they can communicate and behave in accordance with the child's growth and development, continuous supervision is needed to form children's habits. The purpose of this study was to determine Abdullah Nasih Ulwan's education in the education of religious and moral values ​​for early childhood. The method used in this study is qualitative research with the method of literature as the approach used. Data collection used documentation techniques, namely collecting various information related to the research focus, namely Abdullah NashihUlwan's education in religious and moral education. Research from journal articles Sinta 2-5 as many as 15 articles. The research instrument is the researcher himself as the key instrument. Content analysis is used as an analytical technique in research. The findings from this study are that there are 5 methods used in implementing children's religious moral education by Abdullah NashihUlwani, including exemplary methods, habituation, advice, attention and supervision as well as punishment methods. These methods are well applied in children's moral education and then gradually prepare children to become useful people in life.